Land Conflicts in Lampung in 2011-2012 - Wahyu Setyaningsih (Islah: Journal of Islamic Literature and History, 2022)
‘Sadumuk batuk sanyari bumi, ditohi pati’ is a Javanese proverb that implies that land is sacred to someone and some are even willing to sacrifice their lives to own land. The aims of this article include knowing the factors that trigger land conflicts in Lampung, describing the types of agrarian conflicts in Lampung in 2011-2012, and knowing the parties and issues of the conflict. The methodology in this article is a literature study in the form of books, journals, research reports, observations, newspapers, and websites. The data analysis process was carried out descriptively. This writing is arranged systematically starting from the observation of the problem to the recommendation of suggestions to be followed up. Based on the analysis, it can be concluded that the land conflict in Lampung from the 1990s to late 2012 was caused by the original ethnicity of Lampung being displaced by ethnic immigrants as a result of transmigration. The government's incompetence in allocating land to each newcomer has led to land conflicts. Moreover, the existence of private parties who carried out plantation developments in Lampung trigger land conflicts in Lampung, such as the Mesuji Incident.